Criminal Acts Revenge Pornography In Terms Of Indonesian Criminal Law - Dwita Rahmawati; Ifahda Pratama Hapsari; Hardian Iskandar (LEGAL BRIEF, 2022)
Crimes in the form of content containing immorality or sex are increasingly occurring in online networks, one of which is revenge pornography, commonly known as "Revenge Porn." This is a new phenomenon that has emerged alongside the rapid development of technology at this time. Pornography for the purpose of retaliation is a form of coercion and threat to someone, particularly women, to transmit or publish immoral content in the form of photos or videos taken in public by a partner or former partner with the goal of isolating, embarrassing, and destroying the victim's life.This case has been categorized as "online-based emotional violence." The purpose of this study is to find out that revenge porn is a criminal act, to find out and analyze the accountability of the perpetrators of revenge porn according to Indonesian criminal law. This study uses a normative legal research method using a statutory and regulatory approach related to the legal issues being addressed. Based on the results of the study, the perpetrators of the crime of revenge porn can then be held criminally responsible according to the provisions of Articles 281 and Article 282 of the Criminal Code, the Law on Information and Electronic Transactions, and the Law on Pornography.